Interpenetrating dye-functionalized indium–organic frameworks for photooxidative cyanation and oxidative cyclization. Issue 45 (9th November 2022) - Hou, Leixin; Jing, Xu; Huang, Huilin; Duan, Chunying
Abstract : By virtue of light harvesting ability, the O2˙ − generation rate and framework stability of indium–organic frameworks can be precisely regulated by the interpenetrated frameworks making them versatile photocatalysts for photooxidative transformation. Abstract : The structural interpenetration in metal–organic frameworks impacts the porosity designability and tunability of photon absorption; however rationally modifying the functions of MOFs via network interpenetration faces marked challenges. Herein, by carefully modulating the photoactive push–pull chromophore stacking patterns, we report two dye-functionalized indium–organic frameworks, 2-fold interpenetrated In-TPBD-20 and 4-fold interpenetrated In-TPBD-50. Remarkably, the interpenetration of the framework in the In-MOFs facilitates light harvesting ability and hole–electron separation, whereas the introduction of nitrogen sites promotes the adsorption and activation behaviours of molecular oxygen. Theoretical calculations and reactive oxygen species (ROS) assay experiments further reveal that the discriminative interpenetrating behavior of In-TPBD-20 and In-TPBD-50 regulates the generation and proportion of O2 ˙ − and 1 O2 species via spin-flip electron transfer. Due to the moderate light harvesting ability, prominent O2 ˙ − generation rate and higher framework stability, In-TPBD-20 can serve as an efficient robust heterogeneous photocatalyst for various photocatalytic aerobic oxidation reactions, including oxidative cyanation of aryl tertiary amine and oxidative cyclization between aryl tertiary amine and maleimide or electron-deficient alkenes. This work opens a new avenue to regulate the generation of O2 ˙ − and 1 O2 species by the modulation of interpenetrated frameworks, which would elevate MOF photocatalytic oxidation performance.